2016
DOI: 10.1016/j.bpj.2016.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Forces from the Portal Govern the Late-Stage DNA Transport in a Viral DNA Packaging Nanomotor

Abstract: In the Phi29 bacteriophage, the DNA packaging nanomotor packs its double-stranded DNA genome into the virus capsid. At the late stage of DNA packaging, the negatively charged genome is increasingly compacted at a higher density in the capsid with a higher internal pressure. During the process, two Donnan effects, osmotic pressure and Donnan equilibrium potentials, are significantly amplified, which, in turn, affect the channel activity of the portal protein, GP10, embedded in the semipermeable capsid shell. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 104 publications
1
14
0
Order By: Relevance
“…The importance of subtle conformational changes in the context of DNA translocation has also been claimed in modeling studies. In this regard, the distribution of regions differing in the degree of stiffness, thus allowing specific compressions and DNA-dependent distortions, as well as the existence of quasi-equivalent contacts, have been proposed to play important roles in DNA packaging 4345 . Recently, it was also described for bacteriophage P23–45 that the portal may adopt different conformations depending on the stage of virus assembly, with synchronized movements of different domains communicating the inner part of the capsid to the exterior 46 .…”
Section: Discussionmentioning
confidence: 99%
“…The importance of subtle conformational changes in the context of DNA translocation has also been claimed in modeling studies. In this regard, the distribution of regions differing in the degree of stiffness, thus allowing specific compressions and DNA-dependent distortions, as well as the existence of quasi-equivalent contacts, have been proposed to play important roles in DNA packaging 4345 . Recently, it was also described for bacteriophage P23–45 that the portal may adopt different conformations depending on the stage of virus assembly, with synchronized movements of different domains communicating the inner part of the capsid to the exterior 46 .…”
Section: Discussionmentioning
confidence: 99%
“…The RNA inside the viral shell is compact but not pressurised like dsDNA in some bacteriophages [ 182 ]. Nevertheless, it was suggested that viral RNAs are ‘unusually compact’ in order to fit into the limited space of the shell [ 183 ], but calculations show that they are definitely not under pressure [ 184 ].…”
Section: Rna Uncoatingmentioning
confidence: 99%
“…This RNP complex actively transports DNA inside the prohead capsid using energy derived from ATP binding and hydrolysis (6–8). Understanding the mechanism for this molecular motor can provide insights to molecular transport (9), anti-viral therapeutics (10,11) and nanomedicine (12,13).…”
Section: Introductionmentioning
confidence: 99%